SOME FEATURES OF MAWDUDI'S TAFHIM AL-QUR'AN - Mustansir Mir (International Institute of Islamic Thought, 1985)
Abul-A'la Mawdudi (1903-79) was a leading Muslim scholar of the twentieth century. He has written extensively on a variety of Islamic subjects. He wrote in Urdu, but his works, quite a few of which have been translated into other language, have exercised deep influence on educated classes, especially the youth, in many parts of the Muslim world. Though essentially a scholar of the traditional mold, Mawdudi, unlike many other Muslim scholars, is alive to the problems of modernity as they confront the Islamic world. It is this combination of the traditional and modern strains, and his skillful exposition of Islam, that makes him one of the most widely read Muslim authors of today.* Tafhim al-Quran ~ a six volume commentary on the Qur’an, is Mawdudi‘s magnum opus. It is not only a treasury of information, it is also a distillate of Mawdudi‘s thought. In writing Tafhim, as he says in the Preface to the book, Mawdudi has in mind the needs of those educated laymen who wish to understand the message of the Qur’an but lack access to the original Arabic sources on the subject; the word tafhim, which means ”to make someone understand,” aptly describes the nature of the book. The following pages analyze some of the features of the work. A Modern Commentary Even a cursory reading of Tafhim im would show that the work is a “modern” one. Most Urdu Qur’an commentaries present a ”traditional” look in that they lack methodical arrangement of material. Tafhim seems to satisfy many of the formal requirements one expects a book of this kind to meet. A typical page of Tafhim is divided into three portions: one for the Qur’anic text; one for the translation; and one for notes. It is thus possible to read the translation uninterruptedly - a convenience appreciated by those familiar with the irksome pattern of interlinear Urdu translations of the Qur’an. The translation is presented in logical paragraphs. Occasionally, extended quotations are set off from the main text, even given in smaller print. Each volume has a detailed analytical index of subjects treated in the notes. There are 32 maps of historic routes and important geographical locations, and 12 black-and-white photographs, most of them of buildings of Thamudan style of architecture. There are copious cross-references. Again, most of the Urdu Qur’an commentaries employ a highly Arabicized and Persianized idiom that proves to be prohibitive to most common readers. Tafhim  is written in a style that an average reader not only finds comprehensible, but also delightful. Tafhim has been called the first best-selling Urdu ...